2022
DOI: 10.1111/jir.12924
|View full text |Cite
|
Sign up to set email alerts
|

An international field study of the ICD‐11 behavioural indicators for disorders of intellectual development

Abstract: Background The World Health Organization (WHO) has approved the 11th Revision of the International Classification of Diseases (ICD-11). A version of the ICD-11 for Mental, Behavioural and Neurodevelopmental Disorders for use in clinical settings, called the Clinical Descriptions and Diagnostic Requirements (CDDR), has also been developed. The CDDR includes behavioural

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
0
10
0
1
Order By: Relevance
“…Normed standardised instruments for assessing intellectual functioning and adaptive behaviour that are considered the gold standard for use in neurodevelopmental disorders are not universally available (Lemay 2022). This gap may be filled by the ICD-11 behavioural indicators for disorders of intellectual development included in the World Health Organization's new Clinical Descriptions and Diagnostic Requirements (CDDR, formerly Clinical Descriptions and Diagnostic Guidelines) for ICD-11 mental, behavioural and neurodevelopmental disorders.…”
Section: Early Detection and Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…Normed standardised instruments for assessing intellectual functioning and adaptive behaviour that are considered the gold standard for use in neurodevelopmental disorders are not universally available (Lemay 2022). This gap may be filled by the ICD-11 behavioural indicators for disorders of intellectual development included in the World Health Organization's new Clinical Descriptions and Diagnostic Requirements (CDDR, formerly Clinical Descriptions and Diagnostic Guidelines) for ICD-11 mental, behavioural and neurodevelopmental disorders.…”
Section: Early Detection and Screeningmentioning
confidence: 99%
“…This gap may be filled by the ICD-11 behavioural indicators for disorders of intellectual development included in the World Health Organization's new Clinical Descriptions and Diagnostic Requirements (CDDR, formerly Clinical Descriptions and Diagnostic Guidelines) for ICD-11 mental, behavioural and neurodevelopmental disorders. An international field study of the CDDR's behavioural indicators reported that they had excellent inter-rater reliability, good to excellent concurrent validity and good clinical utility, making them particularly useful in identifying individuals with neurodevelopmental disorders in settings where specialised services are unavailable (Lemay 2022).…”
Section: Early Detection and Screeningmentioning
confidence: 99%
“…Outre les principales études décrites ci-dessus, de nombreuses autres études à visées spécifiques ont été menées (par exemple sur les troubles du développement intellectuel et l'autisme [25]). Une autre innovation clé de la CIM-11 DCED a été la participation des patients et de leurs aidants au processus d'élaboration [26].…”
Section: Autres éTudes Sur Le Terrain Sur La Cim-11 Dcedunclassified
“…The study focusing on behavioural indicators for disorders of intellectual devel­op­ment 7 found that these indicators had ex‐­­­­­cel­lent interrater reliability (intra‐class correlations between 0.91 and 0.97) and good to excellent concurrent validity (intra‐class correlations between 0.66 and 0.82) across the four sites where the study was conduct­ed. Furthermore, these indicators were rat­ed as quick and easy to use and app­li­cable across levels of severity; and as useful for treatment selection, prognosis assessment, communication be­tween health care professionals, and education efforts.…”
mentioning
confidence: 99%
“…In the past two years, there have been fur­ther studies focused on other ICD‐11 cate­gories, testing their validity, clinical utility and/or interrater reliability in comparison with the corresponding categories in the ICD‐10 and/or the DSM‐5 5 . Of special interest are four of these studies, dealing respectively with: a) the accuracy in diagnosing mood disorders depicted in case vignettes using ICD‐11 vs. ICD‐10 clinical descriptions and diagnostic guidelines 6 ; b) the interrater reliability, concurrent validity, and clinical utility of the behavioural indicators introduced in the ICD‐11 in order to improve the identification and treatment of individuals with disorders of intellectual development 7 ; c) the sensitivity, specificity, and ability to predict the use of gender‐affirming medical procedures of categories related to gender identity in the ICD‐11 vs. DSM‐5 8 ; d) the clinical utility of the formulation of irritability and oppositionality in youth which has been proposed by the ICD‐11 compared with the corresponding ICD‐10 and DSM‐5 models 9 .…”
mentioning
confidence: 99%